2020
DOI: 10.1111/lsq.12283
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Consequences of Open Candidate Recruitment

Abstract: Candidate‐selection methods (CSM) crucially affect the behavior of Members of Parliament (MPs). Extant research investigates the consequentiality of the selectorate, but is neglecting the candidacy dimension of CSM. But what are the behavioral implications of minimal candidacy‐eligibility criteria (CEC)? I theorize that parties adopt closed CEC in safe districts to ensure nominating loyalist candidates, while they use open CEC in contested districts to attract entrepreneur candidates able to woo decisive swing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This study resonates with recent studies exploring the consequences of lacking proper party socialization including Rehmert (2020a) and Ohmura et al (2018). Both studies show from different angles how the lack of long-term party membership affects MPs behavior and success in parliament.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study resonates with recent studies exploring the consequences of lacking proper party socialization including Rehmert (2020a) and Ohmura et al (2018). Both studies show from different angles how the lack of long-term party membership affects MPs behavior and success in parliament.…”
Section: Discussionsupporting
confidence: 89%
“…For the Japanese case, Smith and Tsutsumi (2014) report that candidates nominated in the wake of public calls for applications mostly lack prior party membership and political experience and that these candidates exhibit political attitudes more moderate when compared to their copartisans selected through more traditional channels. Rehmert (2020a), moreover, finds that Japanese MPs nominated through this open recruitment are less active in parliament.…”
mentioning
confidence: 96%
“…Contributions in the edited volume on candidate selection by Gallagher and Marsh (1988) present cross-sectional information on candidacy criteria, but lack systematic research on the unifying consequences of variations on the candidacy dimension. Limited empirical research has shown that candidates selected through open recruitment following nationwide and formally undiscriminating calls for applications exhibit policy attitudes different from those of co-partisans that were selected through traditional channels (Smith & Tsutsumi, 2014) and that these candidates are less active in parliament than those MPs with a stronger party membership background (Rehmert, 2017). As of now, the theoretical and empirical research on the candidacy dimension is bleak and empirical evidence on its effect on party unity is lacking completely.…”
Section: Introductionmentioning
confidence: 99%
“…First, not all candidate selection processes might be influenced by “fairness rules” or informal networks. This might hold even more true as parties tend to increase “open recruitment” candidate selection processes (Rehmert, 2020a). In such cases, the factors identified by the experiment can play a relevant role.…”
mentioning
confidence: 99%